Frações: estratégias lúdicas no ensino da matemática - Valio, Denise Teresa de Camargo (2014)
The main aim of this master´s degree dissertation is the Mathematics teaching as well as the pedagogical and teaching practices related to the topic of rational numbers, particularly, fractions. The Fractions project, main title of this paper, aims at reaching not only basic education students but also educators with the objective of proposing understandable and attractive ways of teaching the subject matter in focus.The methodology applied in learning rational numbers in their fractional form was achieved through the playful and practical exercises involving two groups of 6th graders in the Fundamental from public schools. The material handling and display of results contribute to the construction of knowledge on Mathematics and consequently its learning. The teaching activities and experiments are the hallmark and engine for the development of this dissertation project due to the fact that the use of manipulable material (graded PET bottles, funnels and water) ensures originality to the teaching/learning relationship of Mathematics.Mathematical concepts such as equivalence and comparison between fractions and even basic operations (addition and subtraction) purposely confine in the teaching sequences carried out in the educational project.